The Economic Consequences of Accounting for Stock Splits and Large Stock Dividends. - Peterson, Craig A.; Millar, James A. (The Accounting Review, 1996)
Abstract Presents a study based on actual accounting treatment and appropriate statutory definitions of distributable equity. Explanation for managers' motivation for declaring large stock distributions and the choice of accounting method; Costly and noncostly methods of accounting.